Relation of smoking, physical inactivity, alcohol consumption and elderly population with mortality from noncommunicable diseases: a worldwide database ecological study (Research, Society and Development, 2023)
Introduction: Noncommunicable Diseases (NCDs) are conditions that result from a multifactorial combination of the individual. They are mainly represented by chronic respiratory and cardiovascular diseases, cancer and diabetes. They are related to some risk factors that increase the incidence of morbidity and mortality, such as smoking, consumption of alcoholic beverages, physical inactivity and the natural aging process. Objectives: to analyze the association between smoking, physical inactivity, aging and alcoholism with NCDs mortality worldwide. Materials and Methods: An ecological observational study was carried out, with the population studied being composed by world regions and countries, with their respective data on the prevalence of mortality from NCDs, prevalence of elderly people aged 65 years and over, smokers, physically inactive and consumption of alcoholic beverages estimated in liters of alcohol per capita. Results: 253 regions and countries available in the world bank were evaluated. The mean prevalence (±SD) of mortality from NCDs was 70.2 (±20.2)%. Evaluating the elderly population, it was noticed that for every 1% increase in its prevalence, there is an increase of 2.3% in NCDs mortality (p